MORPHO-FUNCTIONAL CHANGES IN PITUITARY-ADRENAL SYSTEM AT THE EARLY STAGES OF EXPERIMENTAL DIABETES - Ткачук, Ю.Л. (World of Medicine and Biology, 2014)
After 7 days of experimental diabetes mellitus (EDM) development, reactive changes in the pituitary-adrenal system response to metabolic disorders in the body are detected. In the pituitary gland it is manifested by increased functional activity of corticotropic cells: increase their nuclei area and nuclear-cytoplasmic index, significant growth of bulk density secretory granules in their cytoplasm by bordered granules. Under these conditions, thickening of zona fasciculate, significant decrease of endocrinocytes area due to their degranulation in the adrenal cortex are observed. On 28 day of EDM, stage compensatory processes in pituitary-adrenal system are observed. Growing of bulk density of secretory granules and hydropic dystrophy in corticotropic cells are observed. These qualitative and quantitative changes of corticotropic cells lead to thickening all zones of the adrenal glands, increasing of the profile fields endocrinocytes and nucleis area. Bulk density of lipid droplets in cells also increased.
Keywords: corticotropic cells; adrenal gland; streptozotocin-induced diabetes